Isolation and Identification of NIF Gene Homologue of Locally Isolated Azorhizobium Strains from Stem Nodules of Sesbania Rostrata - Abd Samad, Azman (1997)
Characterisation of UPMR 43, UPMR 44 and X was conducted. Morphological studies of colonies showed that all strains gave a relatively large gummy, watery, translucent or whitely opaque colour on a modified glutamate agar. Intrinsic antibiotic resistance (IAR) patterns of all strains indicated that they were resistant to ampicillin of up to 50 mg/l but susceptible to streptomycin, tetracycline and kanamycin at concentrations of 25, 15 and 10 mg/l, respectively. The growth characteristics of UPMR.43 and UP"MR.44 (in a modified glutamate medium (GM) and peptone medium (PA)) was studied using shake flask method. UPMR43 grew better in GM compared to PA but the reverse was true for UPMR44. PA significantly reduced the cell concentration and affected growth characteristic. The generation times for both strains in both media were less than 6 h indicating that they were fast growers. The banding pattern of total DNA of three strains digested with EcoRI showed that they were very similar. A large plasmid, subject to confirmation was detected in UPMR44 using Hirsch method and one small plasmid in UPMR43 using Casse method. A 13.5 kb BamHI and a 7.0 kb EcoRI DNA fragment from total DNA extracts of all local strains were detected in Southern blot experiments using probes carrying the nifHDK genes of Klebsiella pneumoniae and Azotobacter vinelandii. The results showed that the nif genes of the Azorhizobium strains were detectable using the heterologous nif probes from K. pneumoniae and A. vinelandii. The similar results obtained from colony morphology, generation time, IAR patterns, total DNA restriction patterns and DNA-DNA hybridisation of the three strains studied suggests that they may be the same strain. The obtained results also showed that local strains have a similar characteristics with A. caulinodans ORS571. Strain X may be considered a unique strain since S. rostrata was easily infected although it is not native to Malaysia. It is postulated that this strain may have an alternative host plant.